Intimate partner violence and quality of life of young women in urban slum and non-slum communities, Ibadan, Nigeria - Omowumi O. Okedare; Mobolaji M. Salawu; Olufunmilayo I. Fawole (BMC Public Health)
Abstract Background Intimate partner violence (IPV) is a prevalent public health problem and a significant contributor to morbidity and mortality among women and girls. IPV significantly interferes with individual’s quality of life (QoL). This study examined and compared the relationship between experience of IPV and QoL of young women in urban slums and non-slums communities of Ibadan, Nigeria. Methods The study was conducted in the five Local Government Areas (LGAs) of Ibadan municipal, Oyo State, and employed a cross-sectional design. The study population were 1,050 young women aged between 18 and 24 years, who had ever been or currently was in a relationship. Data were collected using semi-structured and close-ended 97-items questionnaire, adapted from standardized instruments of the WHO VAW study (WHO, 2013) and WHOQOL BREF. Data were analysed using STATA 16. hierarchical multiple regression model was used to describe relationship between the outcome and independent variables. Results The age (21.0 ± 2.1 years) of respondents was the same in both communities. Prevalence of physical (31.4%, 13.4%), psychological (58.6%, 31.5%) and sexual IPV (37.1%, 18.3%) were (p < 0.05) higher in the slums than non-slums, respectively. Overall QoL score was lower among IPV victims than non-victims in both non-slum (67.3 ± 23.4; 72.2 ± 19.8) and slum communities (67.3 ± 23.1 versus 72.4 ± 21.1). Physical and psychological QoL scores were lower (p < 0.05) among IPV victims in both settings. The predictors of overall QoL were experience of any IPV, perceived social support, partner's age, while experience of sexual IPV and partner's age were predictors of psychological QoL. Lastly, the predictors of physical QoL were experience at sexual debut and perceived social support. Conclusion Experience of IPV was common in both communities, with a consequential reduction in the QoL of young women. Measures to improve the QoL of young women need to target reduction of IPV and available social support in both settings.